(untitled) - Miller, Roger LeRoy (New York, 1997)
Designed to provide students with an overview of the basic concepts of money and banking, this work includes pedagogical features such as policy, management and international notebooks, to increase student interest and build understanding of key concepts.
Keywords: Money,Monetary policy,Banks and banking,Tiền,Ngân hàng và nghiệp vụ ngân hàng,Chính sách tiền tệ